Wymiar etyczny w funkcjonowaniu współczesnego przedsiębiorstwa - Teneta-Skwiercz, Dorota (The Measurement of Ethics in the Functioning of Contemporary Enterprises, 2008)
This article focuses on identifying the role of ethics and its significance in modem enterprises. It presents factors determining ethical level in companies and tools which may help when introducing ethics in management. In the last part of the article, the meaning of ethics in Polish business has been presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 18-28